2010
DOI: 10.1149/1.3458648
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Storage Using Conversion Reaction in Maghemite and Hematite

Abstract: We report here on the lithium storage performance of ␣-and ␥-Fe 2 O 3 , undergoing conversion reaction at C/10 and 2C. Both ␣-and ␥-Fe 2 O 3 transform to nanostructured Fe/Li 2 O composite during the first discharge, while the first charge results in the formation of nanosized ␥-Fe 2 O 3 . Such a transition from ␣-Fe 2 O 3 to ␥-Fe 2 O 3 is attributed to its thermodynamics at the nanosize. Better storage performance of ␥-Fe 2 O 3 at 2C compared with ␣-Fe 2 O 3 is attributed to the formation of highly crystallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
44
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 12 publications
4
44
0
Order By: Relevance
“…It has been known that nanosized Fe 2 O 3 particles have superparamagnetic properties. [17] Thus, g-Fe 2 O 3 materials actually showed an identical electrochemical behavior with that of a-Fe 2 O 3 from the second charge-discharge process. [13] Among iron oxides, Fe 2 O 3 usually has four phases, the two main phases being a-Fe 2 O 3 (hematite) and g-Fe 2 O 3 (maghemite).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…It has been known that nanosized Fe 2 O 3 particles have superparamagnetic properties. [17] Thus, g-Fe 2 O 3 materials actually showed an identical electrochemical behavior with that of a-Fe 2 O 3 from the second charge-discharge process. [13] Among iron oxides, Fe 2 O 3 usually has four phases, the two main phases being a-Fe 2 O 3 (hematite) and g-Fe 2 O 3 (maghemite).…”
mentioning
confidence: 76%
“…[12] As shown in Figure 3 f, the hysteresis curve of FNT from a superconducting quantum interference device (SQUID) characterization showed typical superparamagnetic behavior with 58 emu g À1 Iron is the fourth most abundant element on earths crust, and therefore cheap and non-toxic iron-based materials have attracted the recent attention of scientists for use as energy storage materials. [17] One of the notorious problems of iron oxides as anode materials is their rapid loss of discharge capacities during the cycling of lithium ion batteries. [14] Usually, the application of iron oxides as anode materials in lithium ion batteries have focused on a-Fe 2 O 3 , [15] and studies on g-Fe 2 O 3 as anode materials were relatively little explored.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High resolution transmission electron microscopy (HRTEM), selected area electron diffraction patterns (SAED) along with Raman spectroscopy experiments revealed an interesting information. The metastable γ-Fe 2 O 3 has been stabilized in both cases upon Li uptake followed by Li extraction [31]. Though the Gibbs free energy of α-Fe 2 O 3 is relatively less than γ-Fe 2 O 3 in bulk (~ 50 nm), the excess surface contribution arising from nanostructuring (when the grain size is lowered to less than 16 nm ) during the conversion reaction results in energy cross-over, stabilizing the metastable phase of γ-Fe 2 O 3 (as shown in Figure 7).…”
Section: Size Effect and Its Influence On Thermodynamics During Convementioning
confidence: 96%
“…It is also interesting to note that, the conversion of bulk γ-Fe 2 O 3 to nano γ-Fe 2 O 3 requires less energy compared to the conversion of bulk α-Fe 2 O 3 to γ-Fe 2 O 3 (end products being the same). Hence, the excess available energy dissipated in the form of local heat could cause better crystallization of γ-Fe 2 O 3 which favourably influences its lithium storage performance, for details see the discussion in Ref 28. Thus, apart from the electronic conductivity [32], thermodynamic phase stability at nanosize affects the lithium storage by the conversion reaction in α-Fe 2 O 3 and γ-Fe 2 O 3 [31]. However besides thermodynamics at nanosize, our recent experience has revealed that grain connectivity due to various synthetic conditions affect the storage performance of electrode materials significantly (independent of the mechanism of storage processes).…”
Section: Size Effect and Its Influence On Thermodynamics During Convementioning
confidence: 99%